2017
DOI: 10.22159/ajpcr.2017.v10i11.20144
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Chemically Inactivated Salmonella Enteritidis Vaccine in Chickens

Abstract: Objective: Salmonella enteritidis ghosts (SEGs) is a non-living empty bacterial cell envelopes which were generated using a different concentration of sodium hydroxide (NaOH) 6.4 mg/mL and evaluated as a vaccine candidate in specific pathogen-free (SPF) chicken. SEGs have been produced by chemical-mediated lysis and evaluated the potential efficacy of chemically induced SEG vaccine and its ability to induce protective immune responses against virulent S. enteritidis challenge in SPF chickens.Methods: SPF chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Polimun Salmo vaccine developed from Salmonella strains containing immunogenic proteins of the outer membrane of S. gallinarum SG-15 and strains having F-proteins (flagella) and surface PNP lipids of S. typhimurium ST-15 and S. enteritiditis in the structure of the microbial cell 15. The bacterial mass of each strain was converted into protective antigens of formalinized and concentrated cultures of S. enteritidis, S. typhimurium and S. gallinarum with a concentration of each antigen of at least 8 billion microbial bodies in a single dose (El-Safty et al, 2017). Observations of the birds after vaccination showed that none of the immunized animals showed any adverse reactions such as abnormal behaviour, mortality, or signs of anorexia, depression, or diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Polimun Salmo vaccine developed from Salmonella strains containing immunogenic proteins of the outer membrane of S. gallinarum SG-15 and strains having F-proteins (flagella) and surface PNP lipids of S. typhimurium ST-15 and S. enteritiditis in the structure of the microbial cell 15. The bacterial mass of each strain was converted into protective antigens of formalinized and concentrated cultures of S. enteritidis, S. typhimurium and S. gallinarum with a concentration of each antigen of at least 8 billion microbial bodies in a single dose (El-Safty et al, 2017). Observations of the birds after vaccination showed that none of the immunized animals showed any adverse reactions such as abnormal behaviour, mortality, or signs of anorexia, depression, or diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Other group of SPF-ECE S were inoculated with mixture of minimal cytotoxic concentration of different tested extract separately with each virus separately (0.2 mL per egg) for calculation of the antiviral inhibitory concentration fifty (IC 50 ). 27,28 Un-inoculated SPF eggs were always included as control of embryo. The eggs inoculated via allantoic cavity and were incubated for 6 days PI at 37ºC with humidity 60-80%.…”
Section: Inhibition Concentration and Therapeutic Indexmentioning
confidence: 99%
“…HI antibody was recorded in the control vaccinated group received the vaccine without receiving plant extract and other vaccinated treated groups which received the tested extracts separately. 27,28 Compliance with ethics requirements…”
Section: Evaluation Of Immune Boosting Properties Of Different Samplementioning
confidence: 99%